Altered expression of microRNA during fracture healing in diabetic rats. Issue 2 (February 2018) - Takahara, S.; Lee, S. Y.; Iwakura, T.; Oe, K.; Fukui, T.; Okumachi, E.; Waki, T.; Arakura, M.; Sakai, Y.; Nishida, K.; Kuroda, R.; Niikura, T.
Abstract : Objectives: Diabetes mellitus (DM) is known to impair fracture healing. Increasing evidence suggests that some microRNA (miRNA) is involved in the pathophysiology of diabetes and its complications. We hypothesized that the functions of miRNA and changes to their patterns of expression may be implicated in the pathogenesis of impaired fracture healing in DM. Methods: Closed transverse fractures were created in the femurs of 116 rats, with half assigned to the DM group and half assigned to the control group. Rats with DM were induced by a single intraperitoneal injection of streptozotocin. At post-fracture days five, seven, 11, 14, 21, and 28, miRNA was extracted from the newly generated tissue at the fracture site. Microarray analysis was performed with miRNA samples from each group on post-fracture days five and 11. For further analysis, real-time polymerase chain reaction (PCR) analysis was performed at each timepoint. Results: Microarray analysis showed that there were 14 miRNAs at day five and 17 miRNAs at day 11, with a greater than twofold change in the DM group compared with the control group. Among these types of miRNA, five were selected based on a comparative and extended literature review. Real-time PCR analysis revealed that five types of miRNA (miR-140-3p, miR-140-5p, miR-181a-1-3p, miR-210-3p, and miR-222-3p) were differentially expressed with changing patterns of expression during fracture healing in diabetic rats compared with controls. Conclusions: Our findings provide information to further understand the pathology of impaired fracture healing in a diabetic rat model. These results may allow the potential development of molecular therapy using miRNA for the treatment of impaired fracture healing in patients with DM. Cite this article : S. Takahara, S. Y. Lee, T. Iwakura, K. Oe, T. Fukui, E. Okumachi, T. Waki, M. Arakura, Y. Sakai, K. Nishida, R. Kuroda, T. Niikura. Altered expression of microRNA during fracture healing in diabetic rats. Bone Joint Res 2018;7:139–147. DOI: 10.1302/2046-3758.72.BJR-2017-0082.R1.